EVALUATION STUDY FOR SOME AVAILABLE SOIL POTASSIUM EXTRACTION METHODS AND ITS RELATIONSHIP WITH ABSORBED POTASSIUM BY BARLEY CROP - & bdulrasol, Asaad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Two   pots   experiments were  conducted  one of  silty  clay  loam texture  and the other in  loamy  sand  texture   by planting barley crop variety “Samir” to evaluate extraction efficiency of  seven  chemical   extractants via the   correlation with  the   potassium taken up by barley crop. Four  of these extractants were: BaCl2, CaCl2, MgCl2 and NaC l; the remaining three were: CH3COONH4,  NH4HCO3,  NH4HCO3 + DTPA. The study  was  performed by  the application of four  levels of  potassium sulfate  fertilizer (41.5 % K): 0, 50, 100, and 150 kg  K ha-1 in four  replicates using  RCBD design . At  the  end  of  the   agricultural  season, soil   available  potassium  was  extracted  using these extractants.  Plant  samples  (straw+ cereal) were digested to  test K taken up by  plants. Results indicated: that available  potassium increased potassium uptake in both soils with increasing of amount potassium  fertilizer applied. Results of  the study also showed differences in extractants  efficiency  in both soils textures  through correlation  between  K extracted and absorbed. All chlorides extractants  except  Barium  chloride  have shown superiority on ammoniac extractants in fine texture soil while the ammoniac extractants  except CH3COONH4 showed superiorityon chloride  extractants in coarse texture soil.The efficiency of  the extractants  in soils were as follows: in coarse soils NH4HCO3+DTPA > CaCl2 > NH4HCO3 >MgCl2, in fine soils NaCl > MgCl2 = CaCl2> CH3COONH4  This study concluded that calcium chloride extractants   had good efficiency in both soils, followed by magnesium chloride extractant.